PENGARUH LINGKUNGAN TOKO, KUALITAS PRODUK, DAN KEWAJARAN HARGA TERHADAP KEPUASAN PELANGGAN DAN PENGARUH WORD-OF-MOUTH DAN KEPERCAYAAN TERHADAP NIAT PEMBELIAN KEMBALI DI SEPHORA - Anggraeni, Agita Tria; Bernarto, Innocentius (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
The competition in the beauty industry in Indonesia is becoming increasingly intense, as evidenced by the performance differences between Sephora.co.id and Sociolla.com. The higher total visits and rankings of Sociolla.com indicate a significant performance gap. This study aims to examine the effects of Store Environment, Product Quality, and Price Fairness on Customer Satisfaction, as well as the effects of Word-of-Mouth (WOM) and Trust on Repurchase Intention among Sephora's cosmetic store consumers. The research employs a descriptive approach with a quantitative method. Data was collected from 271 respondents via Google Forms and analyzed using SmartPLS 4.0. The results indicate that Store Environment, Product Quality, and Price Fairness have a significant positive effect on Customer Satisfaction, which, along with Word-of-Mouth (WOM) and Trust, also has a significant positive effect on Repurchase Intention. Managerial implications emphasize the importance of improving customer satisfaction, creating Referral Programs to enhance WOM, evaluating pricing strategies, and designing stores with unique layouts to attract more visitors.